Pengaruh Kompetensi Guru dan Reputasi Sekolah Terhadap Kepuasan Siswa Melalui Retensi Siswa SMK Negeri 10 Surabaya - Akmal, Shofwan Naufal; Harianto, Eric (Ikatan Da'i Indonesia, 2024)
This study aims to analyze the effect of teacher competence and school reputation on student satisfaction and retention at SMK Negeri 10 Surabaya. This study uses quantitative methods with Proportional Random Sampling analysis techniques. This study uses a quantitative approach and data collected through questionnaires distributed to students of SMK Negeri 10 Surabaya with a sample of 345 students. Data was obtained through an online questionnaire using Google Form. Hypothesis testing shows that teacher competence has a positive and significant effect on student satisfaction, and student satisfaction has a significant effect on student retention. In addition, school reputation was also found to have a significant influence on student satisfaction. The managerial implication of this study suggests the need for continuous improvement of teacher training programs as well as strengthening school cooperation with universities and industries to improve school reputation and student satisfaction. This study has limitations in the scope of the population that only involves one school so that generalization of the results of this study needs to be done with caution. The benefits of this study can provide insights into teacher competence and school reputation that can be used for further study by academics or practitioners in the field of education and help educators and school administrators to improve their performance.